2019
DOI: 10.1111/ppl.13031
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitrate reductase‐dependent nitric oxide production in magnetopriming‐induced salt tolerance in soybean

Abstract: In the present study, experiments were performed to investigate the role of nitric oxide (NO) in magnetopriming-induced seed germination and early growth characteristics of soybean (Glycine max) seedlings under salt stress. The NO donor (sodium nitroprusside, SNP), NO scavenger (2-[4-carboxyphenyl]-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide, CPTIO), inhibitors of nitrate reductase (sodium tungstate, ST) or NO synthase (N-nitro-L-Arg-methyl ester, LNAME) and NADPH oxidase inhibitor (diphenylene iodonium, DPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 47 publications
2
61
0
Order By: Relevance
“…As NR is a fundamental pathway of NO production, the regulation effect of magnetization on plant development was noted by the accumulation of NO production, especially SMF2 and SMF3. Earlier, Kataria et al, [ 61 ] stated the striking function of NR in the production of NO in response to the magneto-priming of soybean to salt tolerance. This enhancer effect of SMF via NO could be associated with regulation various biochemical pathways as interaction with phytohormones (as modulation auxin content in roots), capturing of ROS (as peroxide and superoxide), attenuation of lipid peroxidation, membrane damage, and the activation of antioxidative responses [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As NR is a fundamental pathway of NO production, the regulation effect of magnetization on plant development was noted by the accumulation of NO production, especially SMF2 and SMF3. Earlier, Kataria et al, [ 61 ] stated the striking function of NR in the production of NO in response to the magneto-priming of soybean to salt tolerance. This enhancer effect of SMF via NO could be associated with regulation various biochemical pathways as interaction with phytohormones (as modulation auxin content in roots), capturing of ROS (as peroxide and superoxide), attenuation of lipid peroxidation, membrane damage, and the activation of antioxidative responses [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of nitrate reductase in nitric oxide production in alleviation of salt stress during seed germination [45] Pre-treatment with SMF in soybean exposed to salt stress also had a positive effect on increasing α-amylase, protease, and NR activities, along with higher levels of H 2 O 2 , O 2…”
Section: Salt Stressmentioning
confidence: 95%
“…Pre-treatment with SMF in soybean exposed to salt stress also had a positive effect on increasing α-amylase, protease, and NR activities, along with higher levels of H 2 O 2 , O 2 •− , and nitric oxide (NO) [ 45 ]. The authors have suggested NO as one of the main signaling molecules in MF-induced salt tolerance in soybean seedlings.…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the role of H 2 S was examined in regulating photosynthesis under overnight frost and daytime high light in avocado (Joshi et al ). Finally, Kataria et al () have reported crucial role of nitrate reductase‐dependent production of NO in regulating magnetopriming‐induced salt tolerance in soybean.…”
mentioning
confidence: 99%